2015
DOI: 10.1111/cei.12644
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-36α axis is modulated in patients with primary Sjögren's syndrome

Abstract: Summary The aim of this study was to investigate the expression of the interleukin (IL)‐36 axis in patients with primary Sjögren's syndrome (pSS). Blood and minor labial salivary glands (MSG) biopsies were obtained from 35 pSS and 20 non‐Sjögren's syndrome patients (nSS) patients. Serum IL‐36α was assayed by enzyme‐linked immunosorbent assay (ELISA). IL‐36α, IL‐36R, IL‐36RA, IL‐38, IL‐22, IL‐17, IL‐23p19 and expression in MSGs was assessed by reverse transcription–polymerase chain reaction (RT–PCR), and tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 26 publications
3
77
0
2
Order By: Relevance
“…This showed that the ocular surface inflammatory reaction of this kind of patients was more serious than that of simple dry eye [19–23]. In this study, we also found that corneal nerve fibers were less and the number of local lymphocytes was significantly increased in IRDE than those in SDE by confocal microscopy scan.…”
Section: Discussionsupporting
confidence: 67%
“…This showed that the ocular surface inflammatory reaction of this kind of patients was more serious than that of simple dry eye [19–23]. In this study, we also found that corneal nerve fibers were less and the number of local lymphocytes was significantly increased in IRDE than those in SDE by confocal microscopy scan.…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, risk of renal and central nervous system involvement was directly correlated with IL‐38 serum levels, and higher detectable baseline levels of IL‐38 in the circulation increased the risk of persistent active disease . A disease related to SLE is Sjogren's disease in which the expression of IL‐38 was found to be upregulated in gland biopsies from patients with primary Sjogren's disease . The IL‐36 axis was proposed in this study to be important for disease modulation in Sjogren, and with IL‐38 being a possible antagonist of IL‐36 signaling similar to IL‐36Ra it might play a significant role in the pathogenesis of this autoimmune disease …”
Section: Role Of Il‐38 In Diseasementioning
confidence: 76%
“…In keratinocytes, blocking IL‐36γ with siRNA or IL‐36 receptor suppressed LL37‐mediated production of IL‐8 as well as CXCL10 . Elevated circulating levels as well as salivary glands of IL‐36a have been reported in patients with Sjogren's syndrome . Histologically, α/β and γ/δ T cells were identified in the salivary glands of the patients.…”
Section: Il‐36mentioning
confidence: 98%